Evaluation of Methanolic Leaf Extract of Parkia biglobosa (African locust bean, Jacg, Benth) Leaves against Trypanosoma evansi - P. Shaba; N. P. Kurade; V. Bhanupraksah; R. K. Singh (Technological Innovation in Pharmaceutical Research Vol. 10, 2021)
In our ongoing research to determine the presence of antitrypanosomal compound(s) from medicinal plant, leaves of Parkia biglobosa were extracted with methanolic solvent at concentrations (250-1000 µg ml-1). Methanolic plant extract (MPE) obtained was tested against Trypanosoma evansi for trypanocidal activity. This was performed on Vero cells grown in Dulbecco’s Modified Eagle Medium (DMEM) and supplemented with foetal calf serum (FCS) 20-40% at appropriate conditions. In vitro cytotoxicity test of P. biglobosa methanolic leaf extract at concentrations (1.56-100 µg ml-1) was done on Vero cells but without FCS. In vitro trypanocidal activity varied from immobilization, reduction and to the killing of trypanosomes in corresponding ELISA plate wells. At 250 µg ml-1of MPE of P. biglobosa, there was drastic reduction of average mean trypanosomes count in the extract (40.±0.0 to 7.000±0.33) as observed. At 500 µg ml-1 of the test extract of P. biglobosa, there was complete killing of trypanosomes (40.±0.0 to 0.00±0.00) at 9 h of incubation, which was statistically the same as diminazine aceturate (50 µg ml-1) at 4 h. Trypanosomes counts decreased in concentration and time –dependent manner with significant difference (P \(\) 0.05 to 0. 01)). MPE of P, biglobosa and diminazine aceturate, standard drug, were cytotoxic to Vero cells except at concentrations of 12.5- 1.56 µg ml-1. Alkaloids, flavonoids, anthraquinones, tannins, phlobotannins and cardiac glycoside already isolated from P. biglobosa leaves and other parts of it could be responsible for higher antitrypanosmal activity.